2021
DOI: 10.1186/s43055-021-00427-y
|View full text |Cite
|
Sign up to set email alerts
|

Placenta accreta scoring system (PASS)—assessment of a simplified clinico-radiological scoring system for antenatal diagnosis of placenta accreta

Abstract: Background Placenta accreta spectrum (PAS) of disorders is an important cause of post-partum hemorrhage and resultant maternal morbidity and mortality. Imaging plays an indispensable role in antenatal diagnosis of PAS. However, diagnosis of PAS on both ultrasonography and magnetic resonance imaging (MRI) is reliant on recognition of multiple imaging signs each of which have a wide range of sensitivity and specificity. There is no single pathognomonic diagnostic feature. This results in interobs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Nevertheless, in some clinics, it is done consistently in all cases with doubted PAS. 10 , 20 , 42 Hence, the diagnosis of PAS requires the availability of multidisciplinary team care with well-experienced radiologists in ultrasound and MRI, histopathologists, obstetricians, nursing staff experts, blood bank, and laboratory specialists to establish the accurate diagnosis and management of PAS. 5 , 24…”
Section: Diagnosis Of Placenta Accreta Spectrummentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, in some clinics, it is done consistently in all cases with doubted PAS. 10 , 20 , 42 Hence, the diagnosis of PAS requires the availability of multidisciplinary team care with well-experienced radiologists in ultrasound and MRI, histopathologists, obstetricians, nursing staff experts, blood bank, and laboratory specialists to establish the accurate diagnosis and management of PAS. 5 , 24…”
Section: Diagnosis Of Placenta Accreta Spectrummentioning
confidence: 99%
“…However, in some clinics, it is required for all patients with doubted PAS. 42 MRI is also used to assist the ultrasound in the evaluation of the placental deepness invasion, the lateral outspreading degree of myometrial and parametrial invasion in doubted features found on ultrasound. 20 MRI has the advantages of sensitivity to blood flow, large imaging range, high soft tissue separation rate, and is not affected by maternal obesity, less amniotic fluid, posterior placenta, and so on.…”
Section: Diagnosis Of Placenta Accreta Spectrummentioning
confidence: 99%
See 3 more Smart Citations